Recent progress on bulk Fe-based alloys for industrial alkaline water electrolysis. Issue 4 (9th January 2023) - Zhou, Pengfei; Bai, Haoyun; Feng, Jinxian; Liu, Di; Qiao, Lulu; Liu, Chunfa; Wang, Shuangpeng; Pan, Hui
Abstract : Bulk Fe-based alloys have high potential for achieving green hydrogen production commercially by AWE. In this review, we systemically summarize recent development on strategies to improve their catalytic activity. Abstract : Alkaline water electrolysis (AWE) is the most mature technology to produce green hydrogen for achieving carbon neutrality. However, the high cost of green hydrogen leads to its low market-occupation rate. The key to improving the rate is to develop low-cost and efficient electrocatalysts that can be easily fabricated on a large scale in industry. Bulk Fe-based alloys stand out because they are cheap, abundant, very stable, and suitable for mass production, leading to high potential for achieving green hydrogen production commercially by AWE. In this review, we systemically summarize recent development on strategies to improve the catalytic activity of bulk Fe-based alloys, including constructing porous structures, alloying, doping, in situ activation, dealloying, corrosion, and anodization. Prospects for the use of bulk Fe-based alloys in industrial AWE are given at the end. We expect that this review can provide guidelines for the manufacturing of bulk Fe-based alloys for the mass production of green hydrogen in AWE.